C-Jun drives melanoma progression in PTEN wild type melanoma cells - Kappelmann-Fenzl, Melanie (Cell Death Dis, 2019)
Due to the critical impact of active AP-1 transcription factors in melanoma, it is important to define their target genes and to identify and ultimately inhibit oncogenic signals. Here we mapped the genome-wide occupancy of the AP-1 family member c-Jun in different melanoma cells and correlated AP-1 binding with transcriptome data to detect genes in melanoma regulated by c-Jun. Our analysis shows that c-Jun supports the malignant phenotype by deregulating genes in cancer-relevant signaling pathways, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K) pathways. Moreover, we demonstrate that the importance of c-Jun depends on melanoma stage and mutation status of the tumor suppressor PTEN. Our study reveals that activation of c-Jun overrules the tumor suppressive effect of PTEN in early melanoma development. These findings help to understand the relevance of c-Jun within cancer pathways in different melanoma cell types, especially in relation to MAPK and PI3K pathways, which are commonly deregulated in melanomas. Consequently, targeting c-Jun in PTEN(+) melanoma cells may represent a promising therapeutic strategy to inhibit survival of melanoma cells to prevent the development of a metastatic phenotype.